Effect of spacing and boron application and spacing on growth, yield parameters and yield of sunflower (Helianthus annuus L.) hybrids in spring season: Effect of spacing and boron application and spacing on growth, yield parameters and yield of sunflower (Helianthus annuus L.) hybrids in spring season - SHELLY NAYYAR DHALIWA,; VIRENDER SARDANA, (Journal of Oilseeds Research, 2023)
A field experiment was conducted during 2020 and 2021 spring season on loamy sand soils to study the effect of boron on sunflower hybrids sown under varied crop geometry. Treatment comprised four hybrids (PSH 1962, PSH 2080, KBSH 44 and KBSH 53) allocated to main plots, three spacings to sub plots (60 cm x 30 cm, 67.5 cm x 25 cm and 67.5 cm x 30 cm) and foliar application of boron (control and 220 ppm) at ray floret opening stage to sub sub plots which were replicated thrice. Hybrid KBSH attained the highest plant height and head diameter. Hybrids PSH 2080 and PSH 1962 produced similar but significantly higher seed yield, oil content and oil yield by virtue of higher number of seeds per plant (except over KBSH 53), seed weight per captulum, 100 seed weight and hectolitre weight than KBSH 44 and KBSH 53 in both years and mean analysis. Spacing of 60.0 cm x 30.0 cm and 67.5 cm x 25.0 cm resulted in similar but higher seed and oil yields than 67.5 cm x 30.0 cm. Foliar application of boron significantly increased the seed yield, oil content and oil yield through improvement in growth and yield parameters over without it application.